(untitled) (ACME, 2024)
The intricate nature of the literary tradition on the early centuries of the life of Rome is well known, and the one on Romulus’ biography, hinged on ambiguous and contradictory information, between lights and shadows, makes the study of his figure fascinating, since antiquity. No exception is made by his disappearance, which presents two main versions: in one the first king of Rome ascended among the gods, in the other he was brutally dismembered by the fury of the patres. In the work here presented an effort has been made to understand from a political perspective the motivations underlying the presence of these two versions on Romulus’ disappearance, which are not just different, but diametrically opposite. The political slant given, intends to justify this duality by exploiting the myth of Romulus within the political evolution and upheavals of the 1st century BC, which became a central object in the republican political debate, both in the struggle between factions and in the clashes between the imperatores who dominated the scene.